Bank Capital : Lessons from the Financial Crisis - Demirguc-Kunt, Asli; Detragiache, Enrica; Merrouche, Ouarda (2012)
Using a multi-country panel of banks, the authors study whether better capitalized banks fared better in terms of stock returns during the financial crisis. They differentiate among various types of capital ratios: the Basel risk-adjusted ratio; the leverage ratio; the Tier I and Tier II ratios; and the common equity ratio. They find several results: (i) before the crisis, differences in capital did not affect subsequent stock returns; (ii) during the crisis, higher capital resulted in better stock performance, most markedly for larger banks and less well-capitalized banks; (iii) the relationship between stock returns and capital is stronger when capital is measured by the leverage ratio rather than the risk-adjusted capital ratio; (iv) there is evidence that higher quality forms of capital, such as Tier 1 capital, were more relevant. They also examine the relationship between bank capitalization and credit default swap (CDS) spreads.